2021
DOI: 10.5194/essd-13-3155-2021
|View full text |Cite
|
Sign up to set email alerts
|

A global compilation of U-series-dated fossil coral sea-level indicators for the Last Interglacial period (Marine Isotope Stage 5e)

Abstract: Abstract. This dataset is a comprehensive, global compilation of published uranium–thorium (U-series) dated fossil coral records from ∼ 150 000–110 000 years ago, as well as associated elevation measurements and sample metadata. In total, 1312 U-series measurements from 994 unique coral colonies are included in the current version of the dataset, all of which have been normalized and recalculated using the same decay constant values. Of these measurements, 444 analyses from 330 colonies are relative sea-level … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 130 publications
0
34
0
Order By: Relevance
“…One of the earliest works reporting LIG sea-level indicators in Southeast Asia was that of Chappell and Veeh (1978), examining coral reef terraces in East Timor (Atauro Island and northern Timor Island) to assess RSL changes within the active tectonic context of the study area. More recent work on the coral reef terraces along the north coast of Timor Island was done by Cox (2009) to constrain the neotectonic evolution and arc-continent collision processes in the region.…”
Section: Timor Islandmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the earliest works reporting LIG sea-level indicators in Southeast Asia was that of Chappell and Veeh (1978), examining coral reef terraces in East Timor (Atauro Island and northern Timor Island) to assess RSL changes within the active tectonic context of the study area. More recent work on the coral reef terraces along the north coast of Timor Island was done by Cox (2009) to constrain the neotectonic evolution and arc-continent collision processes in the region.…”
Section: Timor Islandmentioning
confidence: 99%
“…In their study, Cox (2009) mapped 10 additional sites on Timor Island using differential GPS and provided new U-Series coral ages using mass spectrometry. In Cape Namosain, situated along southwestern Timor Island, Jouannic et al (1988) reported seven steps of raised reef terraces, and in the fifth step (Terrace 5, with reef crest at 44 m above low tide), a coral head in growth position was dated MIS 5e.…”
Section: Timor Islandmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the challenges of any LIG sea-level database is the chronostratigraphic constraints, as developing chronologies for Pleistocene timeframes is outside the reach of radiocarbon dating. Even in low-latitude regions where absolute U-series dating can be applied to palaeo-corals, debate on the age constrains remains (e.g., Chutcharavan and Dutton, 2021). In our study area, the MIS-6 glaciation limit divides the study area and the dataset quite evenly (N=68 within the glaciation limit, N=73 outside).…”
Section: Chronological Challengesmentioning
confidence: 88%
“…Continued refinement of MIS 5a and 5c peak GMSL and regional rates of Quaternary vertical tectonic uplift remains within reach. First, numerical models for glacial isostatic adjustment that adopt "3-D" solid earth models with depth-varying and laterally homogenous viscoelastic structure promise to reconcile observed spatial gradients in RSL highstands and GIA model predictions (e.g., Latychev et al, 2005;Clark et al, 2019). Such numerical advancements offer the possibility of refining GMSL estimates in the absence of further field data collection.…”
Section: Review Of Research Themes On Mis 5a and 5c Rsl Indicators And Future Research Directionsmentioning
confidence: 99%